Verba Emosi Sedih dalam Bahasa Minangkabau: Kajian Metabahasa Semantik Alami - Lubis, Risa Mayuni; Mulyadi, Mulyadi (Lingua Susastra, 2024)
Emotions are an important aspect of human life, and emotion verbs play a key role in conveying emotional experiences. This study aims to analyze sad emotion verbs in Minangkabau using the Metabasic Natural Semantics (MSA) theory developed by Anna Wierzbicka and Cliff Goddard. Through qualitative analysis with a descriptive analytic method, this study identifies and describes sad emotion verbs from dictionaries, literary texts, and interviews with native speakers. The results show that there are several sad emotion verbs, such as “ibo,” “marasai,” and “manangih,” each with specific emotional nuances. This research highlights how the Minangkabau language provides rich terms for expressing sadness and reflects emotional experiences in specific cultural contexts. Using MSA theory, this study makes a theoretical contribution to semantic and linguistic studies and enriches the understanding of the relationship between language and emotion in Minangkabau culture.